2006
DOI: 10.17660/actahortic.2006.719.8
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Cooling by Nir-Reflection

Abstract: Wageningen UR investigated the potential of several NIR-filtering methods to be applied in horticulture. In this paper the analysis of the optical properties of available NIR-filtering materials is given including a calculation method to quantify the energy reduction under these materials and to estimate the contribution for greenhouse cooling. It can be concluded that the optimum NIR-filtering material is still not found but there is good potential for further developments. NIR-filtering multilayer coatings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 9 publications
2
35
0
2
Order By: Relevance
“…This heating effect is desirable during cold periods, but in warm periods the temperature in the greenhouse can increase above levels optimal for crop growth and production. Under Dutch climate conditions, permanent NIR filtering in the cover would increase energy consumption depending on crop and outside climate (Hemming et al, 2005a(Hemming et al, , 2006. Therefore, movable NIR reflecting screens would be more suitable under these conditions to reduce the energy load (or need for cooling) during warm periods.…”
Section: Lightmentioning
confidence: 99%
“…This heating effect is desirable during cold periods, but in warm periods the temperature in the greenhouse can increase above levels optimal for crop growth and production. Under Dutch climate conditions, permanent NIR filtering in the cover would increase energy consumption depending on crop and outside climate (Hemming et al, 2005a(Hemming et al, , 2006. Therefore, movable NIR reflecting screens would be more suitable under these conditions to reduce the energy load (or need for cooling) during warm periods.…”
Section: Lightmentioning
confidence: 99%
“…Heat-barrier or 'heat-blocking' films. Fluid-roof greenhouses filtering out the infrared wavelength bands of the solar spectrum (Van Bavel et al, 1985) paved the way towards the development of heat-barrier films (NIR-reflecting films; Hemming et al, 2006b). These films allow a substantial reduction of the greenhouse heat load (Abdel-Ghany et al, 2001;Sonneveld et al, 2006), and lower risks of conditions of heat stress.…”
Section: Disease and Pests Control ('Uv-blocking')mentioning
confidence: 99%
“…A desk study of Hemming (Hemming et al, 2007) found that permanent NIR filtering in the cover would increase energy consumption in the Dutch climate by 10%, and concluded that movable screens would be more suitable in such conditions. In the experiment whose preliminary results we present here, we compare the effect on the greenhouse climate and crop water use of a NIR reflecting material and a standard material with similar PAR transmission, both installed as movable screens.…”
Section: Introductionmentioning
confidence: 99%